Disaster Risk Management Preparedness and Challenges of a Local Beach and Dive Resort in Southern Negros Occidental - Sangat, Joyce Apple; Estores, Kristin Iris (Technium Business and Management, 2023)
Abstract. Background: This study assessed the extent of disaster risk management preparedness of a local beach and dive resort in Southern Negros Occidental in terms of natural disasters and man-made disasters as assessed by local tourism key players and identified the challenges in the disaster risk management preparedness of the local Beach and Dive Resort and a proposed Disaster Risk Management Preparedness Action Plan based on the findings. Method: The respondents of this study were the DRRM staff, Tourism Office Employees, Community Leaders, Tourists, and Beach and Dive Resort Personnel who were selected using quota sampling for tourists, and complete enumeration was utilized for DRRM Staff, Tourism Office employees, Community Leaders, and Beach and Dive Resort Personnel. This descriptive study utilized a researcher-made survey questionnaire to measure the extent of disaster risk management preparedness and challenges encountered by a local beach and dive resort. Results: The data gathered revealed that the extent of disaster risk management preparedness of a local beach and dive resort in terms of natural disasters as assessed by local tourism key players was found to be of great extent in the typhoon, floods, earthquakes, and landslides in all stages of disaster preparedness (before, during, and after). In terms of natural and man-made hazards, the resort management disaster preparedness was found to be a great extent. The need to develop a "culture on disaster risk management preparedness" of the community and the lack of communication/coordination among the stakeholders involved are the biggest challenges encountered by the tourism key players while preparing for natural hazards. While lack of communication/coordination among the stakeholders involved is the most common challenge encountered while preparing for man-made hazards. Conclusion: This study concluded that resort management needs to consider many factors in disaster risk management preparedness and the challenges they might encounter in preparing for hazards. To be adept with disaster risk management preparedness, the resort management needs to be abreast with the effective coordination and communication between tourism key players by developing a comprehensive directory of these key players that could help in an emergency. More importantly, the resort management must abide by the norms and standards set forth by the DRRM Act to ensure that tourists would perceive that the resort management has low risks. Practical Value of the Paper: This paper has value in the locale of the study and the community. The findings of this study were used in the development of the disaster risk management preparedness action plan for a local beach and dive resort of Negros Occidental in the areas of natural hazards (typhoon/flood and landslide/earthquake) and man-made hazards (crime and terrorism and health threat events). Likewise, the findings of this study significantly contribute to the existing literature on the extent of preparedness of local beach and dive resorts in the different stages and types of hazards.